Analysis regarding the impact of ‘fake news’ on the quality of life of the population in a region affected by earthquake activity. The case of Romania–Northern Oltenia - Mărcău, Flavius Cristian; Peptan, Cătălin; Băleanu, Vlad Dumitru; Holt, Alina Georgiana; Iana, Silviu Adrian; Gheorman, Victor (Frontiers in Public Health, 2023)
The study aims to examine the impact of the wave of seismic activity in the northern region of Oltenia (Gorj County, Romania) in February 2023 and the belief in 'fake news' (circulated regarding causality, manifestations, and future developments of the seismic activity) on the quality of life of the affected population. It was considered opportune to conduct this study, given the novelty of such a situation, as the mentioned geographical area is not known to have a high seismic risk.RESULTS: Our study indicates that individuals who are not concerned, due to their disbelief in "fake news" information, about the possibility of new strong earthquakes in the mentioned area feel the best physically, having an average satisfaction level of 82.80 (with a standard deviation of 19.70) on the WHOQOL-BREF scale. On the other hand, those who believed in the fake news experienced the lowest levels of psychological well-being, with an average satisfaction of 60.80 (and a standard deviation of 21.98). The WHOQOL-BREF is an instrument that assesses the quality of life across four distinct domains, and this study emphasizes the importance of accurate and trustworthy information for people's well-being.The results of the study highlight that the quality of life indicators of people in the geographic area affected by the wave of seismic movements are negatively impacted due to the release of "fake news" in the public domain regarding the cause of seismic movements in Gorj county (and the previous earthquakes in Turkey) and their future manifestations and developments (the possibility of high magnitude seismic movements), as well as the lack of information provided by the public authorities on the issue at hand (causes, effects, future manifestations, management measures).